Performance evaluation of grid connected solar powered microgrid: A case study - Srivastava, Rachit; Amir, Mohammad; Ahmad, Furkan; Agrawal, Sushil Kumar; Dwivedi, Anurag; Yadav, Arun Kumar (Frontiers in Energy Research, 2022)
Besides being limited in quantity, conventional energy sources also emit toxic gases. The Photovoltaic (PV) Solar System is one of the most energizing green energy sources. Around the globe, solar panels are being installed on barren land as well as on the roofs of buildings to generate electricity. An education institute in northern India recently took a step in this direction by installing a grid-tied 100 kWp solar power plant. The installed PV panels are tilted at an angle of 30° and mounted on the roof of the building. The actual PV plant system’s performance differs from the performance under laboratory conditions. Hence, performance evaluation of real outdoor plants becomes essential, especially when the plant is commissioned in different situations, such as roof-mounted systems. Many softwares can estimate the plant’s performance evaluation, but their reliability is not yet proven. This paper examines the performance evaluation of grid-tied PV plants between January 2019 and December 2019 in accordance with the IEC 61724 standard. Moreover, the results of the actual plant have also been compared with the results from the PV*Syst software that simulates the real-time behavior of the plant. Further, in order to evaluate the power plant’s performance, this paper analyzes the various parameters of the PV plant, including reference yield, final yield, and performance ratio of the PV plant. An evaluation of the module’s performance indicates that it has produced 101.57 MWh of energy over 1 year, with a performance ratio of 0.60. It is evident from the comparative analysis that rooftop solar panels are an economically viable and technologically feasible means of providing electricity in the northern parts of India. By taking such measures, the institutes or offices can protect the environment and save money by becoming microgrids. The proposed project provides a roadmap for installing rooftop photovoltaic plants in populated cities without occupying additional land.